Kemudahan Akses Bank Rakyat Indonesia Kantor Cabang Sidrap Unit Tanrutedong - Hatta, Muhammad; Serli (As-Syirkah: Islamic Economic & Financial Journal, 2024)
This article discusses Bank Rakyat Indonesia Tanrutedong Unit, Sidrap branch office, which is one of the banks located on Jalan Poros Pare Sengkang, Tanrutedong Village, Duapitue District, Sidenreng Rappang Regency.  BRI Tanrutedong is one of the largest BRI Sidrap unit branch offices in Sidrap compared to other unit offices, the BRI Tanrutedong Unit office was established in 2007 and began processing at that time.  The BRI Tanrutedong Unit itself is widely used by the public for their needs for transactions both cash and non-cash, not only that, the BRI Tanrutedong Unit provides account openings and provides credit assistance for customers in running their businesses.  The BRI Tanrutedong Unit has a quite strategic location because it is on Jalan Poros close to the Tanrutedong Central market, not only that, the easy road access makes it easier for customers to come to the BRI office if there is something they want to consult.